2016
DOI: 10.1016/j.shaw.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Work-Related Musculoskeletal Disorders Among Butchers in Kano Metropolis, Nigeria

Abstract: BackgroundButchering is often associated with high rates of work-related musculoskeletal disorders (WRMSDs). However, published work on the prevalence of WRMSDs among butchers in Nigeria is scarce. This is important because meat processing practices differ across geographical and cultural locations. This study was therefore aimed at analyzing WRMSDs among butchers in Kano metropolis.MethodsSociodemographic and work-settings information was obtained from 102 male cattle butchers (age, 37.49 ± 11.68 years) throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…Similarities in the findings suggest that WMSDs generally occur at a higher frequency level in a working population. The prevalence in our study was lower than that for a study in Ibadan, Nigeria, where a 1-year prevalence rate of WMSD amongst occupational drivers was 89.3% (Akinpelu et al 2011), whilst a WMSD study on butchers in Kano metropolis in Nigeria reported a point prevalence of 74.5% (Kaka et al 2016). The difference between the prevalence found in our study (68.1%) from that found by Kaka et al (2016), indicate that the nature of the work environment may play a significant role in the prevalence of WMSDs.…”
Section: Discussioncontrasting
confidence: 82%
“…Similarities in the findings suggest that WMSDs generally occur at a higher frequency level in a working population. The prevalence in our study was lower than that for a study in Ibadan, Nigeria, where a 1-year prevalence rate of WMSD amongst occupational drivers was 89.3% (Akinpelu et al 2011), whilst a WMSD study on butchers in Kano metropolis in Nigeria reported a point prevalence of 74.5% (Kaka et al 2016). The difference between the prevalence found in our study (68.1%) from that found by Kaka et al (2016), indicate that the nature of the work environment may play a significant role in the prevalence of WMSDs.…”
Section: Discussioncontrasting
confidence: 82%
“…MSDs are the leading cause of disability [1], [2] among workers impairing body functions, reducing work capabilities, and affecting the quality of life [3], eventually causing significant economic ramifications to the workers [4]. Although a high prevalence of MSDs has been reported in various occupations [5], [6], [7], [8], [9], [10], [11], many employees have to keep working even with pain and discomfort for the income. Hence, these workers are continuously being exposed to a specific occupational hazard, further aggravating their pain conditions and inflicting persistent pain in the musculoskeletal system.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of work related musculoskeletal disorders was reported to be more between the butchers in Kano city and very few only avail the medical facility. Also age was found to be the main risk factor in this regard [2]. The development of musculoskeletal disorders (MSD) is mainly due to awkward and uncomfortable working postures [15].…”
Section: Introductionmentioning
confidence: 99%